Numerical Investigation of Tar Formation Mechanisms in Biomass Pyrolysis - Shuiting Ding; Yifei Wu; Xiaojun Yang; Zongwei Zhang (Aerospace)
This study achieves the particle-resolved modeling of biomass pyrolysis via a novel approach of integrating the Discrete Element Method (DEM) with a semi-detailed chemical kinetic mechanism. By coupling CFD-DEM with a 36-step reaction network, the multiscale interactions between particle-scale hydrodynamics and the formation kinetics of 19 tar components under varying temperatures (630–770 °C) are elucidated. Levoglucosan (44.79%) and methanol (18.64%) are identified as primary tar components. Combined with these, furfural (C5H4O2, 7.22%), methanal (CH2O, 6.75%), and glutaric acid (C5H8O4, 4.20%) account for over 80% of all the tar components. The secondary decomposition pathways are successfully captured, and changes in the reaction rates, as seen in triglycerides (R23: 307.30% rate increase at 770 °C) and tannins (R24: 265.41% acceleration), are quantified. This work provides the ability to predict intermediate products, offering critical insights into reactor optimization.